2019
DOI: 10.3390/rs11151805
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Performances of PERSIANN-CDR Precipitation Product over Huai River Basin, China

Abstract: Satellite-based precipitation products, especially those with high temporal and spatial resolution, constitute a potential alternative to sparse rain gauge networks for multidisciplinary research and applications. In this study, the validation of the 30-year Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks-Climate Data Record (PERSIANN-CDR) daily precipitation dataset was conducted over the Huai River Basin (HRB) of China. Based on daily precipitation data from 182 rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 117 publications
(181 reference statements)
1
13
0
Order By: Relevance
“…For instance, the high estimation of rainfall rates by TRMM 3B42 is consistent with other studies on neighboring regions such as Ethiopia [79], which indicated overestimation of rainfall rates on the highland region of Ethiopia. High rainfall rates produced by PERSIANN-CDR, particularly the low rainfall events, is consistent with other studies from Iran highlands and high region of China [41,80]. A large degree of variability of reanalysis dataset, mainly CFSR, agrees with the result presented by Qiaohong Sun and C. Maio 2017 [81], which covers around 30 global precipitation datasets and mentions the large difference in precipitation estimates, especially in complex mountain areas and high latitude regions.…”
Section: Statistical Estimatorssupporting
confidence: 90%
See 1 more Smart Citation
“…For instance, the high estimation of rainfall rates by TRMM 3B42 is consistent with other studies on neighboring regions such as Ethiopia [79], which indicated overestimation of rainfall rates on the highland region of Ethiopia. High rainfall rates produced by PERSIANN-CDR, particularly the low rainfall events, is consistent with other studies from Iran highlands and high region of China [41,80]. A large degree of variability of reanalysis dataset, mainly CFSR, agrees with the result presented by Qiaohong Sun and C. Maio 2017 [81], which covers around 30 global precipitation datasets and mentions the large difference in precipitation estimates, especially in complex mountain areas and high latitude regions.…”
Section: Statistical Estimatorssupporting
confidence: 90%
“…Estimates of precipitation are produced using the PERSIANN algorithm on GridSat B1 infrared satellite data, and the National Centers for Environmental Prediction (NCEP) stage IV hourly precipitation data are used for training the artificial neural network [19,41]. The adjustment of PERSIANN-CDR is done using the Global Precipitation Climatology Project (GPCP) monthly product version 2.2 (GPCPv2.2).…”
mentioning
confidence: 99%
“…The estimates from VIS/IR can only reflect bulk properties of clouds ignoring the characteristics of cloud morphology and microphysics and hence does not correlate well with gauge precipitation (Ebert et al ., 1996; Joyce et al ., 2004; Sapiano and Arkin, 2009). It is also possible that the actual precipitating region may not be consistent with the cloud shield of the precipitation system (Sun et al ., 2019). It is also observed that heavy precipitation usually occurs at the edges of the cloud system which are characterized by relatively warmer cloud top temperature in comparison to the central core of the clouds (Scofield and Kuligowski, 2003; Behrangi et al ., 2010; Tao et al ., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Type of cloud is closely related to precipitation intensities and can significantly improve the estimates but unfortunately, these are complex three‐dimensional structures and high‐frequency estimates from VIS/IR sensors does not contain much information on this respect. Although the identification of the type of cloud is a complex process, numerous studies have pointed out on its importance (Sun et al ., 2019). Evaporation of hydrometeors from subcloud or cloud base is also a crucial aspect which is ignored in the satellite‐based precipitation estimates.…”
Section: Resultsmentioning
confidence: 99%
“…However, Ashouri et al [38] established the proficiency of PERSIANN-CDR in terms of long-term rainfall-runoff modelling with low bias. In recent years, there has been growing literature in the performance of PERSIANN-CDR daily rainfall product to acquire rainfall information in Asian mountainous regions and assess its efficiency in terms of long-term performance for rainfall and hydrological modelling [32,37,[65][66][67][68][69].…”
Section: Appropriateness Of Gridded Datasets In Compared To Observed mentioning
confidence: 99%